Interaction between the VP2 protein of deformed wing virus and host snapin protein and its effect on viral replication - Sun, Li; Li, Ming; Ma, Yueyu; Huang, Sichao; Ma, Mingxiao; Fei, Dongliang (Frontiers in Microbiology, 2023)
Deformed wing virus (DWV) is one of the causative agents of colony collapse disorder. The structural protein of DWV plays a vital role in the process of viral invasion and host infection; however, there is limited research on DWV. Therefore, we herein screened the host protein snapin, which can interact with the VP2 protein of DWV, using the yeast two-hybrid system. Through computer simulation and GST pull-down and CO-IP assays, an interaction between snapin and VP2 was confirmed. Furthermore, immunofluorescence and colocalization experiments revealed that VP2 and snapin primarily colocalized in the cytoplasm. Consequently, RNAi was used to interfere with the expression of snapin in worker bees to examine the replication of DWV after the interference. After silencing of snapin, the replication of DWV in worker bees was significantly downregulated. Hence, we speculated that snapin was associated with DWV infection and involved in at least one stage of the viral life cycle. Finally, we used an online server to predict the interaction domains between VP2 and snapin, Which provides a theoretical basis for further investigation of its pathogenesis and development of targeted therapeutic drugs.